Pengembangan LKPD Berbasis Contextual Teaching and Learning untuk Memfasilitasi Kemampuan Berpikir Kritis Matematis Peserta Didik SMP/MTs - Reni Restiani; Elfis Suanto; Sakur (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This research is motivated by the importance of students' mathematical critical thinking skills. The facts indicate that the level of critical thinking among Indonesian students still needs to improve, especially in the topics of prism and pyramid spatial structures. This study aims to produce Worksheets (LKPD) based on Contextual Teaching and Learning on the topics of prism and pyramid that are both valid and practical to facilitate the mathematical critical thinking abilities of junior high school students. The type of research employed in this study is research and development, utilizing the 4-D model, which consists of four stages: define, design, develop, and disseminate. Based on the analysis of expert validation sheets, the average validity score of the LKPD is 93.04%, categorized as highly valid. Furthermore, based on the analysis of student response questionnaires in small group trials, the average practicality score of the LKPD is 86.25%, categorized as highly practical. Therefore, the development of LKPD based on Contextual Teaching and Learning on the topics of prism and pyramid to facilitate the mathematical critical thinking skills of junior high school students has met the criteria of both validity and practicality.